PENGGUNAAN STRATEGI INKUIRI DALAM PEMBELAJARAN ISOLASI BAKTERI ASAL MOL DAN PENERAPANNYA SEBAGAI PUPUK HAYATI - Meli Astriani (UNIVERSITAS PGRI MADIUN, 2017)
This study aims to utilize household waste and used MOL (Micro-Organism-Local). MOL is used to assist the process of decomposition in composting. This study aims to isolate the bacterial origin of MOL with media of different organic materials and the application of the isolated bacteria as a biological fertilizer. Stages of research involved isolating bacteria from MOL vegetables, then do purification. The next stage is to identify the bacteria colony morphology that includes forms, cells, and Gram. This research is expected to contribute to the field, namely: the development of science, research methodology. First, for science to improve information research methods, research for further development activities for people who have an interest in the processing of biological fertilizers and organic fertilizers. Second, the methodology how to obtain microbes for use in applied research. The results were obtained bacterial isolates were collected from three kinds of treatment samples MOL namely MOL to-I (waste vegetable, sugar, rice water), II (vegetable waste, brown sugar, rice water), and III (waste vegetable, sugar sand, coconut water). The result of the isolation and purification of bacteria obtained amounted to 79 types of bacterial isolates comprising 23 species of bacteria from the sample MOL to-1, 30 species of bacteria from the sample to the MOL-II, and 24 types of bacteria from the sample to-III. Overall the data obtained from the sample to the MOL-I, II, and III of the highest number of bacterial cells present in the sample to the MOL-II with a number of types of bacteria most. This type of bacteria that is known at the time T0, T1.